2016
DOI: 10.1177/0022034516664509
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Periodontitis Genome-wide Association Study in the Hispanic Community Health Study / Study of Latinos

Abstract: Chronic periodontitis (CP) has a genetic component, particularly its severe forms. Evidence from genome-wide association studies (GWASs) has highlighted several potential novel loci. Here, the authors report the first GWAS of CP among a large communitybased sample of Hispanics/Latinos. The authors interrogated a quantitative trait of CP (mean interproximal clinical attachment level determined by full-mouth periodontal examinations) among 10,935 adult participants (mean age: 45 y, range: 18 to 76 y) from the Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…In that study, the investigators discovered and subsequently replicated the association of rs1537415, located in the glycosyltransferase gene ( GLT6D1 ), with aggressive periodontitis. More recently, Sanders et al reported a significant association of a relatively rare TSNAX‐DISC1 noncoding RNA polymorphism (rs149133391) with chronic periodontitis among Hispanic/Latino people and subsequently replicated it among an independent sample of African‐Americans. Other studies have implicated numerous loci without reaching genome‐wide statistical significance levels and/or demonstrating replication in an independent cohort.…”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 97%
See 1 more Smart Citation
“…In that study, the investigators discovered and subsequently replicated the association of rs1537415, located in the glycosyltransferase gene ( GLT6D1 ), with aggressive periodontitis. More recently, Sanders et al reported a significant association of a relatively rare TSNAX‐DISC1 noncoding RNA polymorphism (rs149133391) with chronic periodontitis among Hispanic/Latino people and subsequently replicated it among an independent sample of African‐Americans. Other studies have implicated numerous loci without reaching genome‐wide statistical significance levels and/or demonstrating replication in an independent cohort.…”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 97%
“…Some of the limitations of genome‐wide association studies for periodontitis are related to the sample size of the study and the inherent complexity in defining the trait. A commonly cited limitation in the periodontal genome‐wide association study literature is the relatively modest sample sizes of individual studies compared with reports for other common complex diseases, ranging between a few hundred and up to 10 000‐17 000 participants . This has been somewhat overcome by the establishment of the Gene‐Lifestyle Interactions and Dental Endpoints consortium and a recent report of periodontitis and dental caries genome‐wide association studies among over half a million individuals .…”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 99%
“…One genetic risk factor, SNP rs149133391 in TSNAX‐DISC1 , has been identified to have genomewide significant association with CP through a Hispanic case‐control GWAS (n = 10 935) with a P ‐value of 7.9 × 10 −9 . rs149133391 also showed association with African American CP subjects (n = 4314) with a P ‐value of 9.1 × 10 −3 through a replication study . Since rare variants occur less frequently, association studies require larger sample sizes to achieve the necessary statistical power.…”
Section: Identification Of Cp Genetic Risk Factors Using Gwasmentioning
confidence: 98%
“…A case‐control GWAS of CP in Hispanic subjects (n = 10 935) identified three rare variants: rs75715012 in NELL1 (MAF: 0.089), rs186066047 in IRXI (MAF:0.003), and rs79308117 in ASHIL (MAF:0.005) with P ‐values of 1.1 × 10 −7 , 1.7 × 10 −7 and 2.8 × 10 −7 , respectively. It also identified one common variant, rs10456847 in RNF144B (MAF:0.330) with a P ‐value of 2.6 × 10 −7 . It is worth noting that despite the small P ‐values, the rare variant associations could be false positives since the sample lacked the statistical power to discover rare‐variant associations.…”
Section: Identification Of Cp Genetic Risk Factors Using Gwasmentioning
confidence: 99%
See 1 more Smart Citation